Heroes, ethics and citizenship - Saravia Salazar, Javier Iván (2024)
In the following lines we seek to approach the heroic figure in his relationship with ethics and citizenship. Highlighting its role in the dissemination of citizen values and the construction of collective identities. The heroic figure emerges in processes of change and crisis that project the desires and values of the society of his time, therefore, reflecting on its creation and dissemination is pertinent in a way affected by global problems, such as «great corruption» and crisis of politics. We must also highlight the complex current context for the generation of collective identities and the dissemination of the heroic figure to finally point out the relationship that these heroic figures have with the generation of positive political emotions, as well as the role of civil society and the media. communication in the formation and dissemination of the heroic figure.